Siting, disassaying and exfilling of the Mamão Dam in Ecuador/RN (Research, Society and Development, 2021)
Over four decades, there has been silting process of the riverbed that flows into the Mamão Dam, which supplies the water needs of the city of Ecuador-RN. This process has been taking place, caused largely by the receipt of mining tailings upstream of the reservoir. Thus, it became necessary the dredging consisting of removing the debris build-up and the bed debris and the riverbanks, offering a free flow to the waters that are intended for, and the excavation of the waste particles and accumulated sediment in the bed reservoir. For this, it was necessary; there were the necessary techniques for the conservation and proper maintenance so that did not occur obstruction of alluvial channel this spring. The work consisted of advice to the Municipality of the City of Ecuador, state of Rio Grande do Norte, where it made a technical feasibility study to recover the amount of previously existing water in the weir, were recovered to meet the population's consumption demand city and county. The study was conducted in 2013 and thus met the revitalization process and also the awareness of miners and miners, as the appropriate place for deposit of tailings stemmed these activities.